Minding Russia's nuclear store. - Mosher, D.E.
Russia's thousands of metric tons of bomb-grade uranium and plutonium and hundreds of thousands of displaced nuclear workers represent a proliferation risk that is impossible to ignore, particularly after smugglers have been caught with weapons grade plutonium. The authors discuss the extent of the problem caused by the break-up of the Soviet Union. Cooperation between the US and Russia on aspects of security of such material is discussed
Keywords: US; Bomb-grade plutonium; Bomb-grade uranium; Displaced nuclear workers; Proliferation risk; Security; Weapons grade plutonium